Avaliação da supressividade do solo a Thielaviopsis sp. - Pereira, Priscilla de Fátima (2015)
The stem-bleeding caused by Thielaviopsis sp. has became cause of extreme concern for farmers, research institutions, technical assistance agencies, and health protection and monitoring agencies. This disease has been spreading and, thus, increasing the quantity of coconut trees and farms affected each year. The search for a sustainable control of this pathogen has become constant over time. In this study, we aimed to evaluate the suppressiveness and / or conduciveness of coconut planting soils of two Brazilian regions, as well as the possible variables responsible for such suppression and / or conduciveness. The influence of soils on Thielaviopsis sp. population was assessed by estimating the percentage of baits of ripe banana colonized by this pathogen on soils. This colonization percentage ranged from 4.61 to 83,08%. Then, based on the Scott Knott means test, samples of five most suppressive soils, and five most conducive soils were collected to estimate their nature, as well as determining factors for suppressiveness and / or conduciveness. Physical, chemical and biological characters were assessed for each sample. The total bacteria parameter was found to be higher in suppressive soils. Fluorescent Pseudomonas was only found in one type of soil. The pH, contents of calcium, sum of bases, effective cation exchange capacity, and bases saturation; as well as the sand textural variable were also found in greater amounts in suppressive soils. Contents of aluminum, iron and clay were higher in conducive soils. In addition, statistically insignificant results were found for other parameters when submitted to the same test.